Moisture absorption and diffusivity of epoxy filled layered-structure nanocomposite - Zaman, Izzuddin; Araby, Sherif; Khalid, Amir; Manshoor, Bukhari (2014)
This paper studies moisture absorption and diffusivity of epoxy reinforced layered structure nanocomposites and its effect on fracture toughness. Two different types of layered fillers employed in the study were clay and graphene platelets, in which both surface layers were unmodified and modified by characterized by swelling analysis and fracture toughness measurement. The outcomes surfactant. The nanocomposites were showed that the moisture absorption and diffusivity decreased with the addition of layered fillers. It was found that the modified graphene platelets and clay outperformed the unmodified layers and neat epoxy in terms of reduction of moisture absorption and diffusivity. The modified graphene platelets reduced the moisture uptake and diffusivity about 30% and 33%, respectively compare to neat epoxy, thus indicates its outstanding performance in barrier applications. However, once the nanocomposites were swelling in the water for 5 days, it is noticed that the fracture toughness of nanocomposites were reduced significantly about 35% in average. Nevertheless, the modified graphene platelets still display the better performance compare to the other samples although there was reduction of fracture toughness.